Partisan Bias in Inflation Expectations - Oliver Bachmann; Klaus Gründler; Niklas Potrafke; Ruben Seiberlich (Center for Economic Studies and ifo Institute (CESifo), 2019)
We examine partisan bias in inflation expectations. Our dataset includes inflation expectations of the New York Fed's Survey of Consumer Expectations over the period June 2013 to June 2018. The results show that inflation expectations were 0.46 percentage points higher in Republican-dominated than in Democratic-dominated US states when Barack Obama was US president. Compared to inflation expectations in Democratic-dominated states, inflation expectations in Republican-dominated states declined by 0.73 percentage points when Donald Trump became president. We employ the Blinder-Oaxaca decomposition method to disentangle the extent to which political ideology and other individual characteristics predict inflation expectations: around 25% of the total difference between inflation expectations in Democratic-dominated versus Republican-dominated states is based on how partisans respond to changes in the White House's occupant (partisan bias). The results also corroborate the belief that voters' misperceptions of economic conditions decline when the president belongs to the party that voters support.
Keywords: C13; D72; E31; P44; 330; inflation expectation; partisan bias; political ideology; voters' perceptions; Blinder-Oaxaca; US president